Coupling Power Generation with Syngas-Based Chemical Synthesis A Process Chain Evaluation from a Power Plant Viewpoint - Forman, Clemens (Springer Fachmedien Wiesbaden : Imprint: Springer Vieweg, 2019)
Coupling power generation with syngas-based chemical synthesis according to the so-called 'Polygeneration-Annex' concept offers economic and technical benefits. Clemens Forman assesses the integration of incoming streams by the Annex plant from a power plant point of view across its full load range. Analyses are done by load-dependent flowsheet simulation. The pulverized lignite combustion power plant process is covered by two generic technical states: an existing 650 MW(el) power plant and a near future 1,100 MW(el) power plant with duo block design and dry lignite co-firing. Modeling comprises both the flue gas path and the water-steam circuit. Appropriate stream interfaces are identified and determined depending on the load status. The technical feasibility of integration can be proven. Contents Material Processing of Coal Reference Case Lignite-Fired Power Plant Modeling of the Part Load Behavior Syngas-Based Annex Plant Coupling of Power Block and Annex Plant Evaluation of Preferential Technology Combination Target Groups Researchers and students in the fields of power plant and energy technologies as well as process engineering Power plant, process, and chemical engineers The Author Clemens Forman worked as a research associate at the Institute of Energy Process Engineering and Chemical Engineering at TU Bergakademie Freiberg in the field of power plant technologies.